Body Image Concerns in Patients With Head and Neck Cancer: A Longitudinal Study - Henry, Melissa; Albert, Justine G.; Frenkiel, Saul; Hier, Michael; Zeitouni, Anthony; Kost, Karen; Mlynarek, Alex; Black, Martin; MacDonald, Christina; Richardson, Keith; Mascarella, Marco; Morand, Gregoire B.; et al. (Frontiers in Psychology, 2022)
Objective. Head and neck cancer (HNC) treatments are known to significantly affect functionality and appearance, leading to an increased risk for body image disturbances. Yet, few longitudinal studies exist to examine body image in these patients. Based on a conceptual model, the current study aimed to determine, in patients newly diagnosed with HNC: 1) the prevalence, level, and course of body image concerns; 2) correlates of pre-treatment body image concerns; 3) predictors of immediate post-treatment body image concerns; and 4) association between body image concerns and levels of anxiety, depression, suicidal ideation, support (i.e., satisfaction with support from physician, social/family wellbeing, and unmet support needs), and alcohol and drug misuse. Methods. Patients newly diagnosed with a primary HNC were assessed using structured clinical interviews and psychometric measures at three, and six months after diagnosis. Primary outcome was 3-month, as it was most salient to body image disturbance. Multiple linear regression analyses were conducted on the potential body image predictors, based on the model. Results. On 218 patients with HNC (72% participation), 68% (n=148) presented some level of body image concerns. Body image concerns pre- and post-treatment were significantly related and significantly increased from pre- to post-treatment. Immediately post-treatment (i.e., at 3 month follow-up), 89% (n=132 of 148) presented some level of body image concerns. Correlates of body image concerns in patients with HNC upon cancer diagnosis (i.e., pre-treatment) included: physical symptom burden, difficulties with communication and eating, coping with the cancer diagnosis using denial, suicidal ideation, and having had a past anxiety diagnosis. When controlling for sociodemographic and medical variables, body image concerns in patients with HNC in the immediate post-treatment were predicted by: baseline body image, physical symptom burden, and neuroticism. Conclusion. This longitudinal study helps identify patients more susceptible to experience body image disturbance following head and neck cancer. Clinicians ought to pay special attention to body image concerns upon cancer diagnosis, physical symptom burden, and neuroticism, and may want to target these factors in future preventive interventions.